Be ExPeRT (Behavioral Health Expansion in Pediatric Residency Training): A Case-Based Seminar - Alison Manning; Matthew Weingard; Jacqueline Fabricius; Alexis French; Mya Sendak; Naomi Davis (Association of American Medical Colleges, 2023)
Introduction Pediatric residents report behavioral or mental health (B/MH) assessment and treatment as a training gap and often feel ill-equipped to address these issues in clinical practice. We developed a novel interactive training program to improve resident confidence in managing common pediatric B/MH conditions. Methods The Be ExPeRT curriculum comprised a half-day interactive seminar on attention deficit hyperactivity disorder, anxiety, depression, and suicidality followed by monthly case-based discussions. Content included didactic material, role-play, and case discussion. The training was optional and open to pediatric or combined medicine-pediatrics trainees. Results Twenty-three residents (70% female) participated in four separate seminars over 2 years. Of the participants attending the seminars, 17 (74%) completed the presurvey, and 16 (70%) completed the postsurvey. Statistically significant improvement was noted in comfort treating major depressive disorder (41% pre, 94% post, p = .002), suicide risk (29% pre, 94% post, p < .001), and anxiety (24% pre, 94% post, p < .001) following program participation. Twelve (75%) of the 16 participants completing the survey rated the training in the top 5%-10% with respect to other resident learning experiences. Discussion We developed this curriculum to enhance trainee knowledge and comfort in addressing common pediatric B/MH conditions in primary care. Significant improvement was noted in self-reported comfort in treating major depressive disorder, suicide risk, and anxiety, and the program was well received. The curriculum can be adapted for use in any training program for primary care providers to provide B/MH education that may be lacking or supplement existing programming.